Cultural Acculturation on the Acceptance of the Role of Chinese Ethnicity in Singkawang City Government - Maisondra (Jurnal Bina Praja, 2023)
The Chinese ethnic community in Indonesia faces challenges in integrating with other groups, including in Singkawang. Singkawang is a positive example of a community where harmony and mutual understanding among ethnic groups have prevailed. Rarely are incidents, whether riots or conflicts related to the Chinese ethnic group, found. Therefore, this study aims to analyze the active role of the Chinese ethnic community in the governance of Singkawang through acculturation. This study was conducted with the direct involvement of the researcher on-site. The study used qualitative-descriptive to understand the phenomenon or events regarding cultural acculturation in Singkawang. Historical, anthropological, and sociological approaches are employed to comprehend this phenomenon. Interviews were conducted with ethnic communities to gather primary data, including the Chinese, Dayak, Malay, and Madurese ethnic groups and the Singkawang local government. Secondary information was collected from various research findings, news sources, and historical documents. The results indicate an active role of the Chinese ethnic community in the governance of Singkawang. Their presence is accepted and supported by all ethnic groups in society as a result of the acculturation process that has been ongoing for some time. More specifically, cultural acculturation has occurred between the Chinese ethnic community and other groups, such as the Malay and Dayak communities. This acculturation has generated positive perceptions among the community. Acculturation has also led to language, material culture, dietary habits, and clothing changes. The direct interaction among diverse groups and shared economic conditions play a role in shaping or influencing this situation.